PERSPEKTIF PENGAMBIL KEBIJAKAN DAN STRATEGI PENGEMBANGAN TANAMAN OBAT ASLI LAMPUNG BERDASARKAN PERSEPSI PEMERINTAH PROVINSI LAMPUNG - Henita Astuti; Ratna Dewi Judhaswati; M Syafrizal; Jekvy Hendra; Azhari Rangga (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Indigenous Medicinal Plants Lampung is a medicinal plant obtained directly from natural ingredients in all regions in Lampung Province, and local policy in developing and preserving it is necessary. The purpose of this research is to know the policy of perspective and strategy of TOAL development based on perception of policy maker in Lampung Province. The study was conducted from May to September 2017 located in Lampung Province. Respondents were determined by purposive sampling by appointing relevant parties on TOAL development activities. The results showed that Internal Factor, the strength among others the use of medicinal plants as an alternative medicine has become a tradition of Lampung society, The weakness factor among others HR is still less creative to create variants of traditional medicine products. External Factors consist of opportunities that can be marketed in the form of processed products that can be marketed domestic scale and national scale; and threats, funds allocated to support the development of TOAL are still limited. Strategy for Developing and Implementing Traditional Medicine and Planning Systems for the Availability of Traditional Medicines Raw Materials in Lampung Province to become National Policy Direction to Support Traditional Health Services, covering a) Cultivation and conservation of TOAL resources, b) efficacy and benefits, c) quality, d) accessibility , e) appropriate use, f) supervision, g) research and development, h) documentation and databases, i) human resource development and j) monitoring and evaluation.